The role of regulatory authority in maintaining financial security in the Indonesian banking sector: A legal framework analysis - Nasution, Emmi Rahmiwita (Trigin Publisher, 2023)
This research aims to look at the Role of Regulatory Authority in Maintaining Financial Security in the Indonesian Banking Sector: A Legal Framework Analysis. By utilizing a multifaceted methodology that includes an examination of regulatory frameworks, case studies, and legal frameworks. The results of this study offer a thorough understanding of the complexities inherent in the regulatory environment governing banking in Indonesia. The clarity, enforceability, and adaptability of the legal framework are critically examined, while historical case studies provide an overview of regulatory reactions and the flexibility of the legal framework. The regulatory review provides a comprehensive analysis of organizational resilience, operational effectiveness, and stakeholder viewpoints. The integration of these findings contributes to targeted recommendations to strengthen the regulatory environment and ensure the continued financial security of the Indonesian banking sector.